Humour advertising: a review and a bibliometrics citation analysis - Hafizah Omar Zaki,; Yusniza Kamarulzaman,; Mozard Mohtar, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this paper is to present review and analysis of citations by journals, papers and authors, co-occurrences of keyword and sub-keywords, and the co-authorship between authors, institutions as well as countries in the field of humour advertising. The number of journal publications in humour advertising has increased and expanded over the years in the field of marketing, communication and business research, but are less being discussed in relation to its citation’s analysis. Therefore, the study has been conducted using a review and a bibliometrics analysis approach. A total of 2300 articles for the study has been extracted from the Web of Science database and reviewed using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-analysed). However, only 1500 were screened and selected for use for the citation analysis. This study contributes in a sense that it provides future researchers with knowledge and information about the worldwide citation’s linkages, and networking between authors, institutions, and research interest in the field of humour advertising. This study also provides insights for researchers to engage in developing novel research ideas that may contribute to expanding the engagement of marketing of humour advertising worldwide.